Towards a UV detector for microfluidic devices - Sharma, Amita (Kansas State University, 2013)
Chemists have been trying to relate the structure and composition of different cereal proteins to their physical properties to better inform their product use for more than 250 years now. Among these cereals, wheat is considered the most important due to its unique ability to form viscoelastic dough and retain gas during fermentation, the latter being important for bread making. This property is due to the endosperm part of wheat that contains proteins mostly gliadins and glutens. It is known that the composition and relative ratio of these proteins is determined by both the growing environment and genetics. Manipulation of the genetics allows one for control of only about 50% of the end use quality of the wheat and the rest is controlled by environment. Currently, the bread making quality of wheat is determined by baking test loaves of bread. This process is time consuming and wasteful. The main goal of this project was to create fingerprints of gliadin proteins for different wheat cultivars as a function of environmental conditions. This would then allow wheat kernels to be analyzed and assessed right after harvest to determine their appropriateness for making the various wheat products. Researchers have tried to create a catalogue of information for individual wheat cultivars by ‘fingerprinting’ the gliadins proteins in wheat using various analytical techniques including capillary electrophoresis (CE). CE offers advantages like high separation efficiency, and faster analysis. Further miniaturization of CE on microfluidic devices has enhanced the speed and efficiency of separation. Furthermore, it is possible to integrate multiple chemical analysis processes like sample preparation, separation and detection in a single microfluidics device. Microfluidic uses micron sized separation channels defined in a glass, quartz or polymer. This dissertation is focused on fabricating multilayer microfluidic devices from Poly(dimethylsiloxane) (PDMS) and using these devices to electrophoretically separate wheat gliadin proteins followed by detection using UV absorption in less than 5 min. PDMS is cheap, easy to fabricate and is optically transparent above ~230nm. Initial results of the UV absorbance detector developed for this device are presented.
Keywords: UV detector for microfluidics; Analytical Chemistry (0486)